Reference Pricing Systems on the Pharmaceutical Market - Maximiliane Unsorg (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Constantly rising expenditures for pharmaceuticals and uninformed consumers require government intervention in firms' pricing strategies. To this end, reference pricing systems are frequently employed as regulatory mechanisms. This paper considers a duopoly market with vertically differentiated firms: a brand-name firm and a firm producing a generic version or a branded copy (depending on competition type). It can be proven that the introduction of a reference price leads to lower equilibrium prices for both firms and that it can induce fiercer competition between brand-name and generic/branded copy firms. Additionally, it can be shown that reference pricing promotes generic usage under sequential price competition. When implementing a reference pricing system, an increased market coverage and, hence, an improved provision of medical supply can be achieved due to the lower prices and the stimulated demand for drugs. Even under a higher supply the consumers' expenditures decrease under reference pricing. Finally, the model proves the superiority of reference prices over price caps and therefore indicates that reference pricing systems should be preferred.
Keywords: I11; I18; L51; 330; reference pricing; pharmaceutical market; copayment; price cap; price competition; consumer expenditure